Back analysis of microplane model parameters using soft computing methods - Kucerova, Anna; Leps, Matej; Zeman, Jan (Computer Assisted Methods in Engineering and Science, 2007)
A new procedure based on layered feed-forward neural networks for the microplane material model parameters identification is proposed in the present paper. Novelties are usage of the Latin Hypercube Sampling method for the generation of training sets, a systematic employment of stochastic sensitivity analysis and a genetic algorithm-based training of a neural network by an evolutionary algorithm. Advantages and disadvantages of this approach together with possible extensions are thoroughly discussed and analyzed.